Heavy Mineral Analysis of the Molasse Sediments, Trans Indus Ranges, Kohat, Pakistan - Abbasi, Iftikhar Ahmed; Khan, Mohammad Asif (Journal of Himalayan Earth Sciences, 1990)
The molasse sediments in the Kohat plateau comprise two coarsening upward sequences, the Rawalpindi and Siwalik Groups, which are further subdivided on the basis of their lithological characteristics into a number of formations. Correlation of these formations across different areas becomes very difficult due to their time transgressive nature. Heavy minerals are a useful tool for such correlations, as each formation is characterized by a particular heavy mineral suite. The Murree Formation of the Rawalpindi Group contains a simple association of heavy minerals, and epidote constitutes bulk of the heavy mineral suite. The epidote content decreases upsection with a corresponding increase in the contents of other minerals and also by the appearance of new minerals. The Kamlial Formation is characteristically rich in tourmaline and garnet. The Siwalik Group, particularly the Shakardarra Formation of the Miocene age, is marked by the introduction of high grade metamorphic and igneous minerals such as amphibole, staurolite and kyanite. Amphibole constitutes the bulk of heavy minerals in the Indus Conglomerate Formation (Miocene- Pliocene age) besides pyroxene, kyanite and staurolite. The mineral chemistry of amphibole and garnet shows that the amphibole was derived mainly from the igneous and metamorphic belts of the Kohistan island arc. The major source of garnet in the molasse sediments is interpreted as the metamorphic belts of the Indian plate exposed along its northern margin. Some garnet in the Indus Conglomerate Formation may have been derived from the Kohistan island arc terrain.